USE OF DIAGRAMS AS INSTRUCTIONAL AIDS IN TEACHING OF GEOMETRICAL CONCEPTS AT SECONDARY SCHOOL LEVEL - MUHAMMAD RIZWAN; SOBIA NASEEM; Syed Muhammad Wasif Raza (State Islamic University of North Sumatra Indonesia, 2018)
Angle is a complex topic defined in a variety of contexts; some define angle to be as a pair of rays coming from a single point, as a rotation about a single point, or in a curve. Due to the multiple definitions of angle students get confused as to what an angle truly consists of. This study paid close attention to the misconceptions high school geometry students’ hold about the concept of angle and how to help them gain a more conceptual understanding of this essential concept with the use of different Diagrams. The main idea behind the conduction of this study is to investigate the effect of use of diagrams as instructional aids on the conceptual understanding of angles. The study hypothesizes that angle can be learned using interactive Diagrams. The results of this study showed that diagrams which based on different A.V aids was shown to be more beneficial for the students who used to clear the concept of angles.